Адміністративно-правові засади здійснення контролю та нагляду у сфері фізичної культури і спорту в Україні : автореферат дисертації - Лукін, Б. П.; Lukin, B. P.; Лукин, Б. П. (Харківський національний університет внутрішніх справ, 2023)
Дисертацію присвячено визначенню сутності та особливостей адміністративно-правових засад здійснення контролю та нагляду у сфері фізичної культури і спорту в Україні, а також опрацюванню напрямів вдосконалення норм чинного адміністративного законодавства у відповідній сфері. Визначаються методологічні засади здійснення контролю та нагляду у сфері фізичної культури і спорту в Україні. Окреслюється адміністративно-правовий механізм організації та здійснення контролю та нагляду у сфері фізичної культури і спорту в Україні. Встановлюються напрямки удосконалення контролю та нагляду у сфері фізичної культури і спорту в Україні.

The thesis is devoted to defining the essence and disclosing the peculiarities of the administrative and legal framework for control and supervision in the field of physical culture and sports in Ukraine, as well as to developing the areas for improving the provisions of current administrative legislation in the relevant area. The author has defined the methodological principles of control and supervision in the field of physical culture and sports in Ukraine. In particular, the author has clarified the essence of physical culture and sports as an object of control and supervision; it has been determined the concept and features of control and supervision in the field of physical culture and sports in Ukraine; the types of control and supervision in the field of physical culture and sports in Ukraine have been outlined; the legal basis for control and supervision in the field of physical culture and sports in Ukraine has been characterized and the place of administrative and legal norms among them has been established. It has been outlined the administrative and legal mechanism of organisation and implementation of control and supervision in the field of physical culture and sports in Ukraine. In this regard, the author has revealed the tasks and functions of control and supervision in the field of physical culture and sports in Ukraine; has defined the subject matter and outlined the limits of control and supervision in the field of physical culture and sports in Ukraine; has outlined the system of subjects of control and supervision in the field of physical culture and sports in Ukraine and has provided a description of their administrative powers; has clarified the range of administrative forms and methods of control and supervision in the field of physical culture and sports in Ukraine. The author has established the directions of improvement of control and supervision in the field of physical culture and sports in Ukraine, namely: the foreign experience of control and supervision in the field of physical culture and sports in Ukraine has been summarised and the possibilities of its use in Ukraine have been studied; promising directions of improvement of administrative legislation regulating control and supervision in the field of physical culture and sports in Ukraine have been established.

Диссертация посвящена определению сущности и особенностей административно-правовых основ осуществления контроля и надзора в сфере физической культуры и спорта в Украине, а также проработке направлений усовершенствования норм действующего административного законодательства в соответствующей сфере. Определяются методологические принципы осуществления контроля и надзора в сфере физической культуры и спорта в Украине. Намечается административно-правовой механизм организации и осуществления контроля и надзора в сфере физической культуры и спорта в Украине. Устанавливается направление усовершенствования контроля и надзора в сфере физической культуры и спорта в Украине.
Administrative and legal principles of control and supervision in the field of physical culture and sports in Ukraine
Keywords: Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; Україна; фізична культура; спорт; адміністративне законодавство; нагляд; контроль; сфера фізичної культури і спорту; зарубіжний досвід; field of physical culture and sports; physical culture; sports; administrative legislation; Ukraine; foreign experience; Украина; сфера физической культуры и спорта